Longitudinal waves in a nonlocal rod by fractional Laplacian. Issue 7 (1st April 2020) - Autuori, G.; Cluni, F.; Gusella, V.; Pucci, P.
ABSTRACT: The article deals with the longitudinal waves in a nonlocal elastic rod. Regarding the nonlocal elasticity the Eringeen model has been assumed; the novelty is that this model is described in terms of the fractional Laplace operator . The standing waves are obtained by numerical solutions of the fractional differential equation in one-dimensional continuum. The obtained results are in accordance with the ones reported in the literature and highlight the dispersion phenomenon. The effects of the nonlocal contribution and of the fractional Laplacian order are also analyzed.